Subvertendo a exclusão escolar: a mediação didática dos gêneros discursivos no ensino da escrita - Wagner Rodrigues Silva (Universidade do Minho, 2005)
Conceived as a teaching object in the textual production activity, the discursive genre is analyzed as mediation instrument for the students learning and development. In this perspective, the need for textual production for specific purposes confers a differential function to writing in the school, which results in the modeling of literacy practices for further writing uses in determined social situations. In the genres modeling scope, the teachers mediated rewriting activity is also characterized as a mechanism to prevent the exclusion of the student promoted by the school.